Analisis Resiko Aplikasi Sistem Informasi Pengelolaan Data Umat Menggunakan ISO 31000 (Studi Kasus: Gereja Katolik Santo Paulus Miki Salatiga) - Diane Junianti; Charitas Fibriani (Journal of Computer and Information Systems Ampera, 2021)
The People's Data Management Information System is an information system that manages people's data from the diocese, parish, regional, to environmental levels. This application is used to input data, update data, and delete data, the application of the Ummah Data Management Information System has risks that will hinder the application, such as unstable internet connections, the latest data and the readiness of human resources who operate the system. The purpose of the research is to minimize the possibility of risk, so ISO 31000 is used to determine the impact of risk, the level of risk, and the treatment of risk needed in a company or organization in conducting the analysis. It is hoped that the existence of ISO 31000 can overcome the risks that will occur now and in the future.